Postmenopausal genital bleeding - Luiz Cavalcanti de Albuquerque Neto; Marair Gracio Ferreira Sartori; Edmund Chada Baracat; Manoel João Batista Castello Girão; Geraldo Rodrigues de Lima (São Paulo Medical Journal)
The study was conducted on 748 women who reported genital bleeding occurring at least one year after the last menstruation. Benign causes were most frequent than malignant causes. Among the benign causes, the most frequent were cervicitis (19,95%), prolapsed uterus with decubitus ulcer (19,41%), dysfunctional hemorrhage (13,29%) and endometrial polyps (12,77%). In the group of malignant causes, cancer of the cervix was the neoplasm most often detected (59,26%); endometrial cancer was next, affecting 29,63%. The cancer of the cervix/ cancer of the body ratio was 2:1. In summary, many causes, both benign and malignant, can provoke abnormal postmenopausal bleeding. Thus, curettage of the uterus should be reserved for doubtful cases, i.e., in situations in which, after all non invasive methods of investigations have been exhausted, the possibility of the occurrence of malignant lesions still persist.